National Cross-Sectional Data on Ideal Cardiovascular Health Among Adults in Mongolia in 2019 - Supa Pengpid (2022)
Background: The study aimed to estimate the prevalence, distribution, and correlates of ideal cardiovascular health (CVH) among individuals (20-69 years) in Mongolia. Method: Cross-sectional data were analyzed from 4,516 individuals (20-69 years, mean age = 42.3 years) who participated in the Mongolia STEPS survey in 2019, who had complete measurement of CVH metrics and no history of cardiovascular disease. Ideal CVH measures included non-smoking, healthy diet, physical activity, fasting blood glucose <100 mg/dL, body mass index (<23 kg/m2), total cholesterol <200 mg/dL, and blood pressure <120/<80 mmHg). Results: The prevalence of five to seven ideal CVH metrics was 27.7% in 2019. Most Mongolians had ideal total cholesterol (77.4%), ideal smoking (67.8%), ideal fasting glucose (73.8%) and ideal physical activity (66.0%), while a lower prevalence was found for ideal blood pressure (42.4%), ideal body mass index (31.4%), and ideal healthy diet (1.8%). The prevalence of poor smoking, poor fruit/vegetable intake, poor fasting glucose, poor blood pressure, and poor total cholesterol was higher in men than in women, while poor physical activity was higher in women than in men, and poor BMI did not differ by sex. In the adjusted logistic regression analysis, older age, male sex, and belonging to the Khalkh ethnic group were negatively associated, and a higher number of adult household members was positively associated with meeting the ideal 5-7 CVH metrics. Conclusions: The proportion of meeting 5-7 ideal CVH metrics was moderate among adults in Mongolia. Primary and secondary prevention programmes should be strengthened to improve CVH in Mongolia, considering identified associated factors.